HUBUNGAN MOTIVASI KELUARGA TERHADAP TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN ODGJ DI WILAYAH KERJA UPT PUSKESMAS AMUNTAI SELATAN - Jamilah, Subhannur Rahman, Dini Rahmayani (AKPER Pemkab Purworejo, 2022)
Background: Mental disorders are still a serious problem in the world. ODGJ tend to have a relapse due to not regularly taking medication. ODGJ needs strong encouragement or motivation from the family because family dynamics play an important role in home care. The family is very necessary in guiding and directing so that the ODGJ patient can take medication correctly and in an orderly manner. Purpose: To determine the relationship of family motivation to the level of adherence to taking medication in ODGJ patients in the working area of ​​the UPT Puskesmas Amuntai Selatan. Method: Quantitative research with cross sectional design. The number of samples in this study was 60 people. Results: The relationship between family motivation and adherence to medication in ODGJ patients in the working area of ​​the UPT Puskesmas Amuntai Selatan (p-value 0.000 <0.05). Conclusion: There is a relationship between family motivation and the level of medication adherence in ODGJ patients in the working area of ​​the UPT Puskesmas Amuntai Selatan. Compliance with taking medication from ODGJ patients cannot be separated from the motivation given by the family. The more the family provides motivation, the more obedient ODGJ is to take medicine. Keywords: Family, Compliance, Motivation, ODGJ